Teen Perceptions of the Promotion of Safer Sexual Practices: A Focus Group Study. Issue 1 (2nd January 2017) - Herrman, Judith W.; Kelley, Andrea; Haigh, Katherine M.
ABSTRACT: Teens' own thoughts on fostering safe sexual practice are important perspectives in promoting adolescent sexual health yet are relatively absent in the literature. This focus group study explored teens' perceptions about the supports and challenges that exist as teens strive to engage in healthy sexual practices. Seventy-five teens participated in 11 focus groups using a semi-structured interview guide. School-based health centers provided the setting and facilitated sample recruitment. Focus groups were audiorecorded and transcribed verbatim. Data were analyzed using the focus group guide as a template and typologies, or clusters of concepts, were extracted to establish teen perceptions of the factors that support and challenge their ability to engage in safe sexual practices. The socio-ecological model provided the framework to identify these factors within the individual, family/parent, relational (peer/partner), community, or societal spheres of influence. Results discussed the importance of parents, the value of confidentiality, respect for teen decision-making, relationships skills, developmental aspects of the adolescent years, and social interpretations of gender. These findings revealed important considerations as adults develop policies, messages, and programs designed to promote safe sexual behavior in teens.